Attitudes Toward And Experiences of Digital Labour by Current and Potential Crowdworkers: A South African Perspective - Chidoori, Cuthbert (Department of Information Systems, 2021)
Digital labour is the creation of new products and services through mainly various digital media forms in exchange for a form of remuneration. Digital labour addresses some of their critical issues in South Africa, such as high unemployment, low income and others. Digital labour initiatives, particularly crowdsourcing and others are thought to provide essential benefits such as flexible working times and skills development. However, digital labour can also bring about drawbacks such as the exploitation of workers and low remuneration. The main purpose of this research is to investigate the attitudes toward and experiences of digital labour in South Africa, with a primary focus on crowdworkers in South Africa. A framework built from certain concepts described in the literature review would be used to guide the research. The main research questions would be concerned investigating how the attitudes and experiences affect the intention to participate, the initial and the continued participation in digital labour. The research data were obtained by conducting an online survey amongst 70 participants who would either be potential or current crowdworkers. The research data were analysed using a mixed methods approach, with quantitative and qualitative analysis techniques being used. From the research data collected, some notable findings that unearthed critical digital labour insights included the relationship between the attitude of personal information security and the initial participation in digital labour. This relationship was found to be considerably significant. Also, the relationship between the barrier of internet access cost and the actual participation in digital labour was not significant which was unexpected in a developing country context. The experiential expectations around a living wage and sharing of knowledge notably had the strongest relationship with the continued participation in digital labour of all the experience aspects. However some survey respondents, according to the qualitative responses, noted that the digital labour wages earned were very little compared to the abundant amount of work they would have to produce and therefore felt they were being exploited in their digital jobs. Other aspects such as client networking opportunities, digital skills and work opportunities had a considerable impact on digital labour experiences for digital workers in South Africa. Some major limitations that impacted the research included limited funding to meet the survey respondents' remuneration demands and difficulty in contacting respondents on crowdsourcing sites. The research yields a valuable contribution to the research community by identifying key theories that affect participation in digital labour. Also, by examining the workers' experiences and motivations, the research could provide critical insights for policymakers, platform owners and crowdworkers to utilise for making business decisions. Considerations for future research could be further explored around this research such as exploring the impact of social security for workers in digital labour to ensure fair work conditions and analysing aspects of digital labour more specifically for impoverished and rural communities.